Combining Facile Synthetic Methods with Greener Processing for Efficient Polymer‐Perylene Diimide Based Organic Solar Cells. Issue 6 (26th April 2018) - Dayneko, Sergey V.; Hendsbee, Arthur D.; Welch, Gregory C.
Abstract: Through ease of scalability and facile synthetic methods, eight N‐annulated perylene diimide dimers with different aliphatic chains are synthesized and evaluated as non‐fullerene acceptors in organic solar cells (OSCs). Optical absorption and emission spectroscopy, and cyclic voltammetry are used to characterize the materials. Variation of the length and topology of the aliphatic chains attached at the pyrrolic N ‐position is shown to have minimal effect on properties in solution. As films, the use of a branched aliphatic chains results in the dimer exhibiting a low energy shoulder in the absorption spectrum and a narrower emission band. OSCs are fabricated and tested in air, at room temperature, using an inverted architecture. The polymer PTB7‐Th is used as the donor and all active layers are processed from 2‐methyltetrahydrofuran. OSC power conversion efficiencies are shown to vary from 3.7%–5.4% for OSCs. The dimer with 2‐ethylhexyl aliphatic chains is selected for optimization because of a high organic solvent solubility and excellent film formation properties. Use of the solvent additive 1, 8‐diiodooctane during film formation lead to an increase in efficiency to 6.6%, while halogen‐free processed OSCs reach 6%. This result offers a simple method for materials side‐chain engineering for the development of OSCs processed in air from eco friendly solvents. Abstract : The "side‐chain" engineering of N ‐annulated perylene diimide (PDI) molecular dimeric materials is presented. Changing the length and topology of the alkyl side chain affects both materials solubility and self‐assembly. Polymer solar cells using the new PDI materials as electron acceptors can be processed from green solvents, in air, at room temperature and exhibit good, reproducible performance.